THE ROLE OF 21st CENTURY TRANSFORMATIVE LEADERSHIP: UNDERSTANDING THE PROBLEMS OF THE PANCASILA DEMOCRATIC SYSTEM - Rustan Effendi, Yulius; Iswahyudi, Didik; Samapati, Cevin Samapati (Universitas Islam Negeri Raden Intan Lampung, 2024)
Transformative leadership as a paradigm that continues to develop in the context of the 21st century offers unique thinking in understanding and facing various challenges related to democracy today. This article aims to investigate the role of transformative leadership in the 21st century in interpreting Pancasila democracy and overcoming multiple problems that arise in the context of democracy in student organizations. Through transformative leadership, this article offers solutions based on empowerment, active participation, and capacity building of members. Transformative leadership encourages creating an inclusive environment where individuals have a voice that is valued and heard. This creates a strong foundation for resolving conflict, strengthening trust, and encouraging ongoing engagement. This article uses qualitative researchers with a descriptive approach. Thus this article concludes that transformative leadership has great potential to be a facilitator in dealing with the problems of democracy in the contemporary era. Through this approach, it is hoped that student organizations can build a stronger foundation for an inclusive, dynamic, and sustainable democracy.